2019
DOI: 10.1590/1089-6891v20e-47184
|View full text |Cite
|
Sign up to set email alerts
|

Queijo Artesanal Produzido No Sul Do Rio Grande Do Sul: Avaliação Físico-Química, Microbiológica E Suscetibilidade a Antimicrobianos De Isolados De Staphylococcus Coagulase Positiva

Abstract: Resumo Objetivando o conhecimento do queijo colonial artesanal produzido na região Sul do Rio Grande do Sul, foram analisadas 30 amostras adquiridas no comércio local e feiras quanto às características físico-químicas, além das análises microbiológicas exigidas pela Agência Nacional de Vigilância Sanitária (ANVISA), isolamento de Yersinia enterocolitica e resistência aos antimicrobianos de isolados de Staphylococcus coagulase positiva, obtidos a partir destas amostras. Os valores medianos resultantes das análi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
0
2
0
9
Order By: Relevance
“…The lack of standardization for production of some artisanal cheeses in addition to deficiencies found during processing, such as cases of herd mastitis, poor hygiene during milking and manufacturing, and inadequacy in storage, outlet, and trading conditions, negatively affect the microbiological quality of the food product. Numerous studies reported the presence of S. aureus in Brazilian cheeses, with counts of up to 10 5 cfu/g, considered above the limit allowed by local legislation (<10 3 cfu/g; Brant et al, 2007;Zaffari et al, 2007;Kamimura et al, 2019a;Tavares et al, 2019). These figures are alarming because, at such concentrations, there might be enterotoxin formation by S. aureus, representing a real health risk for consumers.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of standardization for production of some artisanal cheeses in addition to deficiencies found during processing, such as cases of herd mastitis, poor hygiene during milking and manufacturing, and inadequacy in storage, outlet, and trading conditions, negatively affect the microbiological quality of the food product. Numerous studies reported the presence of S. aureus in Brazilian cheeses, with counts of up to 10 5 cfu/g, considered above the limit allowed by local legislation (<10 3 cfu/g; Brant et al, 2007;Zaffari et al, 2007;Kamimura et al, 2019a;Tavares et al, 2019). These figures are alarming because, at such concentrations, there might be enterotoxin formation by S. aureus, representing a real health risk for consumers.…”
Section: Discussionmentioning
confidence: 99%
“…The high moisture content was also reflected in the a w of the samples, which varied between 0.93 and 0.94. High a w is a factor that directly interferes with microbial development, especially the growth of pathogenic microorganisms (Tavares et al, 2019).…”
Section: Physicochemical Analysis During Storagementioning
confidence: 99%
“…Na região sul, o queijo artesanal tipo colonial feito de leite cru, é o principal queijo produzido por famílias rurais (Carvalho et al, 2019). Este tipo de queijo é elaborado com basicamente três ingredientes: leite cru, coalho e sal (Tavares et al, 2019). As principais características do queijo colonial são cor amarelo-palha, casca fina quando possui pouco tempo de maturação ou mais grossa quando sofre uma maior maturação, casca uniforme e lisa, e diferentes dimensões e olhaduras (Kamimura et al, 2019).…”
Section: Introductionunclassified